205k views
3 votes
Please ANswer!!!

x^2 +25 + 2 = 2x^2 + 30
Will mark brianliest!


Solve, please!!!

2 Answers

1 vote

Answer:

x^2 +25 + 2 = 2x^2 + 30

X^2 + 27 = 2X^2 + 30

- 27 - 27

X^2 = 2X^2 + 3

-X^2 = 3

X = SQRT. - 3

User Anthony To
by
4.6k points
3 votes

Answer:

± sqrt(3) i =x

Explanation:

x^2 +25 + 2 = 2x^2 + 30

Combine like terms

x^2 + 27 = 2x^2 +30

Subtract x^2 from each side

x^2 + 27 - x^2 = 2x^2 - x^2 +30

27 = x^2 +30

Subtract 30

27-30 = x^2

-3 = x^2

Taking the square root of each side

±sqrt(-3) = sqrt(x^2)

±sqrt(-3) =x

±sqrt(-1) sqrt(3) =x

We know the square root of -1 = i

± sqrt(3)i =x

User Georgepiva
by
4.9k points